1994
DOI: 10.1099/00221287-140-6-1403
|View full text |Cite
|
Sign up to set email alerts
|

A spore-lytic enzyme released from Bacillus cereus spores during germination

Abstract: The exudate of fully germinated spores of Bacillus cereus IF0 13597 in 0.25 M sodium phosphate buffer, pH 7-08 was found to contain a spore-lytic enzyme. This enzyme was found to cause loss of absorbance in coat-stripped spore suspensions and phase-darkening of the spores but had minimal activity on isolated peptidoglycan substrates. The enzyme was purified in an active form and identified as a 24 kDa protein which is either an amidase or a peptidase. The amino-terminal 19 residues had the following sequence: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 16 publications
(11 reference statements)
5
79
0
Order By: Relevance
“…The peptidoglycan binding motif of SleB is conserved many peptidoglycan hydrolases as mentioned above, while each hydrolase varies in the substrate specificity. The germination-related enzymes, such as SleB and SleC, recognize and hydrolyze only peptidoglycan with muramic δ-lactam moiety (Makino et al, 1994, Miyata et al, 1995a. The identification of the residues in the motif of the germination enzymes responsible for the recognition and/or binding to the muramic δ-lactam structure requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The peptidoglycan binding motif of SleB is conserved many peptidoglycan hydrolases as mentioned above, while each hydrolase varies in the substrate specificity. The germination-related enzymes, such as SleB and SleC, recognize and hydrolyze only peptidoglycan with muramic δ-lactam moiety (Makino et al, 1994, Miyata et al, 1995a. The identification of the residues in the motif of the germination enzymes responsible for the recognition and/or binding to the muramic δ-lactam structure requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…The muramic δ δ δ δ-lactam structure of cortex is crucial for the proper localization of SleB In our previous study, it was shown that SleB degrades only intact cortex but not the muramic δ-lactam-deficient cortex (Makino et al, 1994), suggesting that muramic δ-lactam is a major specific determinant of SleB as a germination lytic enzyme. Therefore, we assumed that muramic δ-lactam might play an important role in the localization process of SleB as well as in the substrate specificity of the enzyme.…”
Section: Construction Of Cwldgere Mutantmentioning
confidence: 99%
See 1 more Smart Citation
“…Germination has been studied in an array of Gram-positive spore-forming species including Clostridium perfringens (Chen et al, 1997;Miyata et al, 1995), Bacillus thuringiensis (Hu et al, 2007), Bacillus subtilis (Ishikawa et al, 1998;Kodama et al, 1999;Moriyama et al, 1996a), Bacillus megaterium (Foster & Johnstone, 1987;Setlow et al, 2009), Bacillus cereus (Chen et al, 2000;Makino et al, 1994;Moriyama et al, 1996b) and B. anthracis (Heffron et al, 2009(Heffron et al, , 2010Lambert & Popham, 2008;Liu et al, 2004). The B. anthracis germination cascade begins when nutrient germinants contact receptors within the spore.…”
Section: Introductionmentioning
confidence: 99%
“…The enzymic hydrolysis of spore-cortex peptidoglycan is essential for spores to complete rehydration during germination and to commence outgrowth. Spore cortex-lytic enzymes have been purified from spores of Bacillus megaterium (Foster & Johnstone, 1987), Bacillus cereus (Makino et al, 1994 ;Moriyama et al, 1996b ;Chen et al, 2000a, b) and Clostridium perfringens (Miyata et al, 1995), and were reviewed by . Based on structural analysis of spore peptidoglycan and its dynamics during germination, Atrih et al (1998 have suggested that there are at least three different types of enzyme activities involved in spore-cortex hydrolysis and modification during germination : glucosaminidase, lytic transglycosylase, and a possible non-hydrolytic epimerase.…”
Section: Introductionmentioning
confidence: 99%